2022
DOI: 10.55275/jposna-2022-0024
|View full text |Cite
|
Sign up to set email alerts
|

Local Infiltration Anesthesia with Liposomal Bupivacaine Decreases Postoperative Narcotic Consumption in AIS

Abstract: Background: Our previous standardized postoperative pain management plan for AIS patients undergoing PSF included the placement of an epidural (EPI) catheter by the spine surgeon prior to fascial closure. The epidural was used for 24 hours, in conjunction with a multi-modal post-operative pain protocol. Local Problem: The 2020 COVID-19 pandemic highlighted the need for our surgical AIS patients and their families to have private rooms/bathrooms. Epidural catheters require arterial line blood pressure monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In a quality improvement study, McIntosh et al retrospectively reviewed 159 AIS patients undergoing PSF and found that patients who received LB required significantly less morphine equivalents than patients who received an epidural catheter with continuous infusion of ropivacaine. 21 They also found the administration of LB was associated with quicker time to ambulation (6 to 7 hours). Our results had similar findings in terms of decreased opioid consumption, as well as mobility, as patients ambulated a mean of 335 feet further on POD 2 when LB was injected locally at the time of surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a quality improvement study, McIntosh et al retrospectively reviewed 159 AIS patients undergoing PSF and found that patients who received LB required significantly less morphine equivalents than patients who received an epidural catheter with continuous infusion of ropivacaine. 21 They also found the administration of LB was associated with quicker time to ambulation (6 to 7 hours). Our results had similar findings in terms of decreased opioid consumption, as well as mobility, as patients ambulated a mean of 335 feet further on POD 2 when LB was injected locally at the time of surgery.…”
Section: Discussionmentioning
confidence: 97%
“…In a quality improvement study, McIntosh et al retrospectively reviewed 159 AIS patients undergoing PSF and found that patients who received LB required significantly less morphine equivalents than patients who received an epidural catheter with continuous infusion of ropivacaine 21 . They also found the administration of LB was associated with quicker time to ambulation (6 to 7 hours).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing pool of evidence supporting nonopioid medications, including intravenous acetaminophen, liposomal and nonliposomal bupivacaine, steroids, and muscle relaxers in both the intra and postoperative time periods for the reduction of postoperative opioid use 7,23 . Of these medications, liposomal bupivacaine was found to have the largest individual-associated decrease in postoperative opioid use while accounting for other intraoperative medications, echoing a growing pool of recent literature supporting liposomal bupivacaine in the pediatric spine population 6,15 . Patients in the TRC cohort, in addition, received statistically significantly greater amounts of the majority of other nonopioid intraoperative medications, with significant association with decreased postoperative MME when accounting for all other variables found in methocarbamol and dexmedetomidine, in addition to liposomal bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid medications are commonly prescribed for pain management after surgery in pediatric populations, 8 despite known risk factors including persistent opioid use and overdose 9–12 . While previous studies have focused on various pain management regimens in the early postoperative timeframe, 13,14 more recent studies have evaluated the effects of intraoperative pain regimens on postoperative outcomes 15,16 . In efforts to manage postsurgical pain and minimize in-hospital opioid consumption and length of stay, multimodal analgesic regimens, including nonopioid regional anesthetics, have been proposed 6,17 …”
mentioning
confidence: 99%
See 1 more Smart Citation